2+4(5x-4)=9-4(2x+1)

Simple and best practice solution for 2+4(5x-4)=9-4(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2+4(5x-4)=9-4(2x+1) equation:


Simplifying
2 + 4(5x + -4) = 9 + -4(2x + 1)

Reorder the terms:
2 + 4(-4 + 5x) = 9 + -4(2x + 1)
2 + (-4 * 4 + 5x * 4) = 9 + -4(2x + 1)
2 + (-16 + 20x) = 9 + -4(2x + 1)

Combine like terms: 2 + -16 = -14
-14 + 20x = 9 + -4(2x + 1)

Reorder the terms:
-14 + 20x = 9 + -4(1 + 2x)
-14 + 20x = 9 + (1 * -4 + 2x * -4)
-14 + 20x = 9 + (-4 + -8x)

Combine like terms: 9 + -4 = 5
-14 + 20x = 5 + -8x

Solving
-14 + 20x = 5 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-14 + 20x + 8x = 5 + -8x + 8x

Combine like terms: 20x + 8x = 28x
-14 + 28x = 5 + -8x + 8x

Combine like terms: -8x + 8x = 0
-14 + 28x = 5 + 0
-14 + 28x = 5

Add '14' to each side of the equation.
-14 + 14 + 28x = 5 + 14

Combine like terms: -14 + 14 = 0
0 + 28x = 5 + 14
28x = 5 + 14

Combine like terms: 5 + 14 = 19
28x = 19

Divide each side by '28'.
x = 0.6785714286

Simplifying
x = 0.6785714286

See similar equations:

| 144=-6(6a+6) | | x^6-9x^3+6=0 | | 4(x+5)=8x+7-4x+13 | | 5(x+3)-2(x+4)= | | -3=-17-x-x | | 17x+19y=23 | | 9x-9=9(x+2) | | .5(x+200)=.56x-356 | | .4(4z+5)+18.4=.6(4z-6) | | 4w^4-22w^3-12w^2=0 | | .88y+3=y-.6 | | x-5/6-2=x-8/5 | | -10(-12-6m)=60m-12 | | x-3/2-3=x-1/3 | | -7+4x=3x-2 | | C-3=-6 | | 3x-10=11+2x | | X+8/11-1/11 | | q+12=9q+9 | | -0.8(x+1)=0.2(x+2) | | 11(z+2)-4(z-3)=4(z-4)+2(z-2) | | 30=-x+45 | | x-0.05x=60 | | -4(5t-4)+7t=8t-3 | | -4(5t-4)+7t=-3 | | 6m/2a | | 12/80=x/100 | | 6m/2m | | 9/x=63/28 | | 3.5=9x/x+13 | | 3(5+8r)=-r+15 | | (3x+4)/(2x-7)=5 |

Equations solver categories